Exposure to hyperbaric oxygen induces tumour necrosis factor-alpha (TNF-alpha) secretion from rat macrophages. - Lahat, N (1995)
We investigated the secretion of TNF-alpha by monocytes and macrophages derived from the peripheral blood, spleen, and lungs after a single exposure to a therapeutic profile of hyperbaric oxygen (HBO). Rats were exposed for 90 min to either 100% oxygen at 0.28 MPa (2.8 atmospheres absolute) or air. Immediately after exposure, mononuclear cells were isolated from blood, spleen, and lungs and cultured for 18 h. The secretion of TNF-alpha from the cultured monocytes/macrophages was determined with and without stimulation with lipopolysaccharide (LPS). Exposure to hyperbaric oxygen induced a significant increase in the spontaneous ex vivo secretion of TNF-alpha (without LPS) by mononuclear cells from the blood, spleen, and lung (P < 0.05 from air controls). Stimulation with LPS after exposure to HBO induced a significant increase in TNF-alpha secretion by lung and spleen macrophages compared with air controls (P < 0.05). However, absolute TNF-alpha levels were not significantly higher than those achieved 'spontaneously' in macrophages exposed to HBO without LPS. Stimulation with LPS induced a marked increase in secretion of TNF-alpha from blood monocytes after exposure to air, but not after exposure to HBO. These results provide evidence in support of a role played by TNF-alpha in mediating HBO effects on different tissues and their immune responses.